Potassium Adsorption Phenomenon in Calcareous Soils of Shahrazur Plain - Saeed, Kamil Sabir (Kurdistan Journal of Applied Research, 2021)
A laboratory study for adsorption of potassium (K) determination was conducted on six soils located in Sharazur plain from the Kurdistan Region of Iraq in 2021 using the batch technique method. Potassium (K) adsorption isotherms were achieved by equilibrating 5.0 g of soil samples with eight grades of K (0 to 300 mg L-1) as KCl in 50 ml of 0.01M CaCl2 solution. To match the data of adsorption, Freundlich, Langmuir, and Temkin adsorption isotherms were used. The results show that the amount of adsorbed K ranged between (45.78 to 52.49) % added K. The Freundlich model fit the equilibrium K adsorption data better for the Serwan location of soil (silty loam), as demonstrated by a greater coefficient of determination (R2 =0.90). The value of heterogeneity factor 1/n for the Freundlich model ranged from (0.34 to 0.47) kg mg-1, which was less than one. The sorption processes for all of the studied soils were normal adsorption. The constant of the Langmuir isotherm (KL) aligned from (0.107 to o.425) L mg-1. Smaller KL values mean that more adsorbed K would be transformed to a non-exchangeable form, either through the creation of crystalline K or through ion occultation. The RL values indicate the type of isotherm, the values of RL> 1 that means the adsorption nature to be unfavorable. The Temkin equilibrium binding constant (AT) was high for all studied soils except the soils of Bestan Sur and Grdigo locations, the high value of AT indicates high binding energy. The Temkin constant (bT) ranged from (10.46 to 13.47) J mole-1 that was related to the nature of the adsorption energy, a positive value indicates that the adsorption process is exothermic.